Penerapan Model Collaborative Problem Solving untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik - Alfarisi, Alfath; Elfizon, Elfizon (Jurnal Pendidikan Teknik Elektro, 2024)
This study was conducted to increase students problem-solving abilities by implementing the collaborative problem-solving model. This study uses quantitative methods in the form of a pre-experimental design with a one-group pretest-posttest design. The population of this study was class X students majoring in Electrical Power Installation Engineering SMK Dhuafa Padang. The sample for this study was students of class X TITL B SMK Dhuafa Padang. This study uses an instrument in the form of written essay test questions which are arranged based on the material and learning objectives to be achieved following the curriculum. In this study instrument testing was carried out to determine the validity and reliability of the questions. The data analysis technique used is the N-Gain test. Based on the results of the research and discussion that has been carried out it shows that the average posttest score obtained is greater than the average score obtained in the pretest and the N-Gain test score is 0,59 which is in the medium category. So it can be concluded that the application of the collaborative problem-solving model can improve students problem solving abilities.